Moroccan tax potential: Econometric analysis through the tax effort - BOUSSELHAMI, Nezha; HAMZAOUI, Moustapha (Turkish Economic Review, 2018)
Abstract. This paper aims to analyse the Moroccan tax potential compared to a sample of countries (panel), relying on the tax effort concept, wich allows isolating the part of the government public levying. It is an international study, using a panel data (25 countries-26 years). The result of econometrics estimations shows the positive effect of the GDP per capita, the openness degree of the economy, the monetization degree and the part of industrial Added Value on the public potential while the part of agricultural Added Value had a negative impact. Analyzing the tax effort, we find that Morocco had a negative effort between 1990 and 2004. But, since 2005, the policies pursued after the reform helped reverse the trend to achieve a positive effort. It means that Morocco exploits all his fiscal resources from the standard of the sample. Keywords. Tax burden, Tax potential, Tax effort, Structural factors, Panel. JEL. E62, G28, H21, C50.